2008
DOI: 10.1523/jneurosci.0141-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into Aberrant Topological Patterns of Large-Scale Cortical Networks in Alzheimer's Disease

Abstract: Recent research on Alzheimer's disease (AD) has shown that cognitive and memory decline in this disease is accompanied by disrupted changes in the coordination of large-scale brain functional networks. However, alterations in coordinated patterns of structural brain networks in AD are still poorly understood. Here, we used cortical thickness measurement from magnetic resonance imaging to investigate large-scale structural brain networks in 92 AD patients and 97 normal controls. Brain networks were constructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

106
873
9
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 891 publications
(1,006 citation statements)
references
References 89 publications
106
873
9
4
Order By: Relevance
“…Thus, nowadays, several studies about functional networks have been carried out to explore the dysconnectivity of AD from neurophysiological signals (He et al 2009;Joudaki et al 2012;Stam et al 2007, Stam 2010. Recent studies have proposed that AD is characterized by the conversion from small-world network architecture to less optimal functional topologies (SanzArigita et al 1994;He et al 2008;Supekar et al 2008). Our findings also support this idea.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, nowadays, several studies about functional networks have been carried out to explore the dysconnectivity of AD from neurophysiological signals (He et al 2009;Joudaki et al 2012;Stam et al 2007, Stam 2010. Recent studies have proposed that AD is characterized by the conversion from small-world network architecture to less optimal functional topologies (SanzArigita et al 1994;He et al 2008;Supekar et al 2008). Our findings also support this idea.…”
Section: Discussionsupporting
confidence: 88%
“…These results resemble past research on functional connectivity strength using graph-based analyses [10,12,13,15]. In these studies, longer path lengths were found in MCI [12] and mild AD [10,13], reflecting disrupted interactions of distant brain regions.…”
Section: Disrupted Functional Coupling Of Prefrontal and Parietal Dmnsupporting
confidence: 88%
“…While earlier studies report altered functional connectivity in AD patients, the precise pattern remains ambiguous, ranging from increased to decreased to no change in global connectivity and lower or no change in local connectivity in AD patients relative to healthy controls (HC) [8][9][10][11][12][13][14][15]. These studies focused on whole brain or predefined regional connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Using the same method as Achard and colleagues (Achard et al 2006), Supekar and colleagues ) have demonstrated that resting-state fMRI-derived functional brain networks in AD show a loss of small-world properties. In contrast to a previous EEG study ) and a structural MRI study (He et al 2008), Supekar and colleagues (2008) found that the loss of small-world properties in AD were characterized by a significantly lower clustering coefficient. This may indicate a disrupted local connectivity, not a significantly longer path length as the earlier two studies reported.…”
Section: Topological Properties Of the Brain Networkmentioning
confidence: 78%